As plantas, o povo e a cultura na comunidade Passagem da Conceição, Várzea Grande, Mato Grosso, Brasil - Fiebig, Gabriela de Ávila (2017)
The rescue of ethno-cognition awakens in science the importance of the wisdom of traditional peoples in search of empirical information about the connection between plants and the human being. The present work aims at recovering the wisdom about the use of local plants by the residents of the community of Conceição, Várzea Grande, MT focusing on the ethnobotanical aspects. The methodological procedure used combined qualitative and quantitative aspects: the qualitative technique used the snowball technique with pre-test application, semi-structured and unstructured interview, photographic record, guided tour, oral history and direct observation; The quantitative model demonstrated the Informant Consensus by calculating the Loyalty Level (NF), Correction Factor (FC) and the Percentage of Major Use Agreement (Pcup%). The reproductive and / or vegetative structures of the plants were collected, identified and deposited in the Central Herbarium of the Federal University of Mato Grosso. The collections were carried out from May 2015 to May 2016, with monthly frequency. The informants cited 187 plant species distributed in 64 botanical families. The cataloged species were distributed in ethnocategories of medicinal use (70%), food (22%) and other uses (8%). The most representative families were: Lamiaceae (8%), Fabaceae (7%), Rutaceae and Asteraceae with 6% each, being 60% exotic and 40% native, in four landscape units: backyard, gallery. The melon-de-são-caetano (Momordica charantia L.) stood out for its relative value of agreement for the main use with 100%. The management of backyards is carried out by the family itself at least once a week and only natural agricultural inputs are used. The cultivation of different species, the management, the purpose and the form of use portray the needs of the family subsistence with little environmental impact. The empirical knowledge accumulated over the years is transmitted to the next generations in day-to-day life through family life and is perhaps the greatest wealth of the community. The cultural manifestations are expressed at all times by the typical cuisine of the Cuiabana Basin and by the faith and devotion to Our Lady of the Immaculate Conception.